Media and Truth in the Perspective of the Practice and Life Form of the Modern “Homo Medialis” - Gáliková Tolnaiová, Sabína (Communication Today, 2025)
The author of the article speaks about epistemological relevancy or rather correctness of media-offered contents, trying to understand the nature of media ‘truth’. She bases her viewpoint on the assumption that these qualities are influenced by the general practice and ways of media production. Essentially, she identifies two forms of practice – the one applied by media professionals and the one typical for amateurs and common people using the Internet. These approaches differ in the ways media content is created and the truth criteria are applied. They represent two different media worlds, each one with its own ‘rules of the game’ and ‘truth regime’. Finally, the author examines what kind of “homo medialis” is required by these pluralist media worlds – or, in other words, how this “homo medialis” should interact with various versions and structures of media reality and truth. The author believes people should employ ‘transversal’ rationality. Homo medialis should then be a person with free will; their ars vivendi should incorporate and nourish certain ‘counter-actions’ that would fight a rather spontaneous tendency to automatically believe mediated information and thus accept the totalitarian claim offered by (one of) incomplete images and associations, i.e. fight against claims that the presented media truth is the absolute and unquestionable one. The author believes that this ars requires constant questioning of what the (media) truth is.